(untitled) (International journal of artificial intelligence, 2026)
This study explores the interplay of agency and fate in two emblematic medieval romance traditions: the Western legend of Tristan and Isolde and the Eastern Uzbek folk epic Tohir and Zuhra. By situating both narratives within their respective cultural and historical contexts, the article examines how notions of destiny, free will, and social obligation shape the trajectories of the protagonists. The analysis highlights the tension between individual desire and collective duty, revealing how agency is constrained by familial honor, political alliances, and supernatural forces. Special attention is given to gender dynamics, showing how male and female figures embody different degrees of autonomy and resistance within the framework of romance. Through comparative poetics, the study investigates symbolic motifs—such as poison, illness, dreams, and omens that encode the inevitability of fate while simultaneously offering moments of human choice. The findings suggest that while both traditions converge on the tragic inevitability of love, they diverge in their cultural interpretations of agency: Western romance emphasizes the destructive power of passion against feudal duty, whereas Eastern epic underscores the endurance of love within communal and moral boundaries. This comparative inquiry contributes to broader discussions in philology, folklore, and literary studies, offering insights into how medieval romance reflects universal human concerns across diverse cultural landscapes.